2012
DOI: 10.1161/circulationaha.112.112912
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrate Supplementation Improves Revascularization in Chronic Ischemia

Abstract: Background-Revascularization is an adaptive repair mechanism that restores blood flow to undersupplied ischemic tissue. Nitric oxide plays an important role in this process. Whether dietary nitrate, serially reduced to nitrite by commensal bacteria in the oral cavity and subsequently to nitric oxide and other nitrogen oxides, enhances ischemia-induced remodeling of the vascular network is not known. Methods and Results-Mice were treated with either nitrate (1 g/L sodium nitrate in drinking water) or sodium chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 51 publications
5
68
0
Order By: Relevance
“…Further, in addition to direct vasodilatory effects, nitrite has been reported to have preconditioning-like effects in settings of ischaemia-reperfusion injury in different tissues 58 through NO-and cGMP-independent mechanisms, 59 and orally administered nitrate has been shown to improve revascularization in chronically ischaemic limbs and decrease platelet activity. 60,61 At the cellular level, nitrite has been shown to inhibit mitochondrial ROS generation and decrease leukocyte recruitment at sites of inflammation. 62 More recently, Dejam et al found that nitrite is a relatively potent and fast vasodilator at near-physiological concentrations and, interestingly, that nitrite functions as an endocrine reservoir of NO by producing remote vasodilation, with a selective preference for oxygendeprived territories.…”
Section: Nitrate Tolerancementioning
confidence: 99%
“…Further, in addition to direct vasodilatory effects, nitrite has been reported to have preconditioning-like effects in settings of ischaemia-reperfusion injury in different tissues 58 through NO-and cGMP-independent mechanisms, 59 and orally administered nitrate has been shown to improve revascularization in chronically ischaemic limbs and decrease platelet activity. 60,61 At the cellular level, nitrite has been shown to inhibit mitochondrial ROS generation and decrease leukocyte recruitment at sites of inflammation. 62 More recently, Dejam et al found that nitrite is a relatively potent and fast vasodilator at near-physiological concentrations and, interestingly, that nitrite functions as an endocrine reservoir of NO by producing remote vasodilation, with a selective preference for oxygendeprived territories.…”
Section: Nitrate Tolerancementioning
confidence: 99%
“…21 We and others have recently demonstrated that exogenous supplementation with near physiological nitrite doses has implications for tissue protection under pathological conditions. This pertains to single nitrite injections, chronically administered nitrite, 17,[22][23][24][25][26][27][28][29] and remarkably also to nitrite administered before the onset of ischemia. 26 Finally, we recently demonstrated that nitrite contributes at physiological levels to the mechanisms causing vessels to dilate when challenged with hypoxia.…”
mentioning
confidence: 99%
“…23,24 Therefore, therapeutic angiogenesis remains an unmet medical need. However, a tremendous interindividual variability exists in the degree of new collateral formation in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%